Challenges and Prospects of Youth Entrepreneurship Development in a Designated Community in the Western Cape, South Africa - Gwija, Saphetha Appie; ., Chux Gervase Iwu (Journal of Economics and Behavioral Studies, 2014)
In a job-scarce environment, where unemployment is rife the need for fostering entrepreneurship especially among youth is a prime concern. This is arguably the case in South Africa, where despite a number of government-pioneered interventions, the level of youth entrepreneurship, particularly in township areas remains unsatisfactory. This study takes a two-pronged approach to establish specific factors that are inhibiting youth entrepreneurship development, and determine the prospects of youth entrepreneurship development in Khayelitsha in the Western Cape, South Africa. The data was collected via self-administered questionnaires that were distributed to 132 respondents, which were randomly drawn from a population of 200 youth entrepreneurs registered on the database of a local organisation which promotes and develops entrepreneurship in the Western Cape. The findings revealed, among others, that a major inhibiting factor to entrepreneurship development is the lack of awareness and inaccessibility of youth entrepreneurship support structures and initiatives in this community. Interestingly though, this hindrance does not appear to have a negative bearing on the identified growing enthusiasm of the youth to engage in entrepreneurial activities. Overall, on the basis of the challenges and prospects revealed, recommendations to improve the current situation are made. This study is an applied research effort and its relevance is linked to the fact that it provides rare insight into the state of youth entrepreneurship in a large but under-researched township community in the Western Cape. The findings and recommendations therefore bear far-reaching ramifications for all stakeholders who are concerned about developing youth entrepreneurship in this society.